Bibliometric Analysis of Sustainable Leadership Using the Visual Mapping Technique - Şengür, Dönüş (Asya Publishing and Consultancy, 2023)
Sustainable leadership is a necessity to achieve the goals of sustainable development, such as addressing complex global issues, preserving environmental and social balance, ensuring the well-being of future generations, and promoting innovation. Sustainable leadership in education is important to contribute to sustainable development goals by equipping future generations with environmental, social, and economic responsibilities and integrating sustainability principles into the education system. This study aims to determine the current state of research containing the term "sustainable leadership" by conducting a bibliometric analysis using the Web of Science (WoS) database. The VOSviewer software is employed to visually represent the data obtained from the WoS database. According to the comprehensive bibliometric analysis results, research related to the theme of "sustainable leadership" began to emerge in 2002, with a total of 390 publications identified in the period from 2002 to 2023. The majority of these publications are in the form of articles, reflecting the interest and curiosity within academic circles in this field. However, considering the lower presence of other document types such as conference papers, book chapters, and review articles, there appears to be a growing need for these types of sources. The bibliometric analysis reveals that research on sustainable leadership is predominantly published in the form of articles, with a significant increase observed, particularly in publications from 2019. The VOSviewer analysis of the "sustainable leadership" field categorizes the most commonly used terms into three clusters: "sustainability", "sustainable leadership", and "leadership". In terms of the distribution of articles in the field of sustainable leadership by citing countries, the countries with the highest number of citations are Thailand, South Africa, the United States, and China, respectively. The findings of the analysis are believed to contribute as a resource for future research and benefit researchers in exploring potential topics related to the theme of sustainable leadership in the near future. Additionally, it is noted that there is limited research on sustainable leadership in Turkey, and recommendations are provided for its further development. © 2023, Asya Publishing and Consultancy. All rights reserved.
Keywords: Bibliometric analysis; Leadership; Sustainability; Sustainable leadership; VOSviewer